Impact of increasing retirement age on longevity factor: an empirical study for government pensioners in Malaysia - Rose Irnawaty Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2012)
Most contemporary research indicates that life expectancy in most countries is increasing. Since average life expectancy tends to increase over time for males and females, mortality risks tends to be smaller over time. Therefore, it is expected that pensioners will tend to live longer and cause an increase in pension liabilities to the government in the future. The government is looking for solutions to decrease the effects of increased longevity on pension costs. The most common changes recommended are to equalize the retirement age for males and females; and to increase the age of retirement. Since pensions are paid for the rest of pensioner’s life; and to the spouse and child of the pensioner (if any) in the form of a derivative pension in the event of the death of the pensioner, the longevity factor can be considered as an important element when constructing an effective Government Pension Scheme. This paper estimates the longevity factor for case of government pensioners who survives and also dies at the particular age of retiement; and examines the impact of increasing retirement age on longevity factor. Based upon the findings, the overall longevity factors for a government pensioner who survives and dies are observed to decreases as retirement age increases.